PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF UNTUK MENINGKATKAN KEMAMPUAN BAHASA DAN KOGNITIF PADA ANAK USIA DINI ( Studi Pada Kelompok A Kelurahan Talang Ulu ) - Titik Harliza; Nina Kurniah (DIADIK, 2020)
This study aims to develop interactive media to improve language and cognitive skills in early childhood. The research method used was the Borg and Gall Research and Development (R&D) method with 10 development steps. Based on the results obtained, it can be concluded: (1) Based on the validation of media experts and material experts, this interactive media falls into the "very feasible" category to be used to improve language and cognitive skills. (2) The use of interactive media can improve early childhood language skills, in terms of listening and speaking. The results of small group trials are included in the "good" category and the results of large group trials are included in the "very good" category. (3) The use of interactive learning media can improve early childhood cognitive abilities. The results of the small group trial were in the "very good" category. In the large group trial, it was included in the "very good" category